Energy Subsidy Reform. - Clements, Benedict J. (International Monetary Fund, 2014)
Energy subsidies have wide-ranging economic consequences. Although they are aimed at protecting consumers, subsidies aggravate fiscal imbalances, crowd out priority public spending, and depress private investment, including in the energy sector. Subsidies also distort resource allocation by encouraging excessive energy consumption, artificially promoting capital-intensive industries, reducing incentives for investment in renewable energy, and accelerating the depletion of natural resources. Most subsidy benefits are captured by higher-income households, reinforcing inequality. Even future gene.